Facial nerve disorder: a review of the literature. Issue 7 (August 2018) - Davies, James; Al-Hassani, Fawaz; Kannan, Ruben
Abstract : Facial nerve disorders present with varying levels of facial dysfunction. Facial nerve reinnervation techniques aim to correct this by attempting to reestablish the connection lost between the facial nerve nucleus and its distal branches, or by using donor nerves to provide an alternate neural input to the facial nerve. Many facial nerve disorders exist; however, tumors and trauma to the facial nerve are the 2 causes that most commonly result in the patient being considered for reanimation procedures, as they most often result in facial nerve discontinuity. Reinnervation techniques are the first line surgical intervention for facial paralysis when a direct connection between the facial nerve cannot be reestablished, with the XII-VII nerve transfer being the most reliable and having the most predictable outcome when compared with the alternative VII-VII procedure. However, when the reinnervation time window is missed, other techniques of reanimation must be used in an attempt to best restore the normal symmetry and function of the face. The modifications to the XII-VII nerve transfer technique have made it the most popular of all methods; however, there are still many other nerves that may be considered as donors, giving the surgeon other options in the event of the hypoglossal (XIIth) nerve being unsuitable.